2001
DOI: 10.1007/s007020170088
|View full text |Cite
|
Sign up to set email alerts
|

Skin function and skin disorders in Parkinson’s disease

Abstract: Cutaneous symptoms (seborrhoea and hyperhidrosis) in Parkinson's disease were investigated. In 70 treated patients with Parkinson's disease and 22 control subjects, non-invasive bioengineering methods (sebumetry, corneometry, pH) were carried out on the forehead, sternum and forearm. In addition, concomitant dermatoses and medication were recorded. 18.6% of the patients had seborrhoea on the forehead (>220 microg/cm2), 51.4% showed normal sebum values (100-220 microg/cm2) and 30% a sebostasis (<100 microg/cm2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 14 publications
0
37
0
1
Order By: Relevance
“…3,4 Other authors have shown that even minimal levels of voluntary activation of the target muscle significantly reduce the degree of inhibition produced by subthreshold conditioning stimuli delivered at ISIs between 1 and 6 msec. [5][6][7] This finding is probably due to reduced excitability of the inhibitory interneurons that project to the corticospinal neurons responsible for activation of the target muscle. 5 Recently, Fisher and colleagues (2002) demonstrated that the short interval intracortical inhibition (SICI) produced with an ISI of 1 msec is functionally distinct from that produced with an ISI of 2 to 3 msec.…”
Section: Appendixmentioning
confidence: 93%
See 1 more Smart Citation
“…3,4 Other authors have shown that even minimal levels of voluntary activation of the target muscle significantly reduce the degree of inhibition produced by subthreshold conditioning stimuli delivered at ISIs between 1 and 6 msec. [5][6][7] This finding is probably due to reduced excitability of the inhibitory interneurons that project to the corticospinal neurons responsible for activation of the target muscle. 5 Recently, Fisher and colleagues (2002) demonstrated that the short interval intracortical inhibition (SICI) produced with an ISI of 1 msec is functionally distinct from that produced with an ISI of 2 to 3 msec.…”
Section: Appendixmentioning
confidence: 93%
“…[5][6][7] This finding is probably due to reduced excitability of the inhibitory interneurons that project to the corticospinal neurons responsible for activation of the target muscle. 5 Recently, Fisher and colleagues (2002) demonstrated that the short interval intracortical inhibition (SICI) produced with an ISI of 1 msec is functionally distinct from that produced with an ISI of 2 to 3 msec. When the ISI is set to 2.5 msec, the threshold conditioning stimulus intensity that produces inhibition is approximately 56% RTh, and inhibition is completely abolished by voluntary activation of the target muscle.…”
Section: Appendixmentioning
confidence: 93%
“…In fact, scalp thickness has been reported as a factor in the development of infection and/or erosion complications [4,12] , and previous work has found that the skin of PD patients can thicken [17] . Furthermore, PD patients are more likely to have skin and subcutaneous tissue diseases [18,19] .…”
Section: Discussionmentioning
confidence: 99%
“…However, hypohidrosis was frequently found in patients having autonomic findings such as orthostatic hypotension or impotence [5,6,12,16,29]. As for hyperhidrosis, the autonomic findings such as orthostatic hypotension, increased salivary secretion, a feeling of hyperthermia, and edema of a lower limb were found more frequently in those with hyperhidrosis than in those without hyperhidrosis in our report [5].…”
Section: Relations With Dyshidrosis and Other Autonomic Disturbancesmentioning
confidence: 78%
“…There is only one report in which is not a clinical symptom in any patient [8], but many reports indicate that a sweating disturbance occurs from 30 % to 50 % of patients with Parkinson's disease [5,6,[9][10][11][12][13][14][15][16][17][18][19][20][21][22]. The report that listed hyperhidrosis and hypohidrosis in separately found that hyperhidrosis varies from 10 % to 100 %, while hypohidrosis is present from 0 % to 40 % of patients.…”
Section: Frequency Of Dyshidrosis (Table 2)mentioning
confidence: 97%